Study of Suicidal Death due to Hanging in District Prayagraj, U.P. (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
Hanging is one of the common methods of commiting suicide and it is considered suicide unless contrary is proved. The present study was conducted at the mortuary of Swaroop Rani Nehru Hospital associated with Moti Lal Nehru Medical College Prayagraj (U.P.), from 1st March, 2020 to 28th February, 2021. Total 299 cases of hanging were found in this duration. The different aspects of hanging cases like sex ratio, age group involved, ligature material used, position of knot, features of ligature mark, point of suspension, type of hanging and other Postmortem findings have been discussed in detail in this study.
Keywords: Suicide; Hanging; Ligature mark